Hemostatic effects of kyukikyogaito in dienogest treatment - H. Takagi; S. Yamada; J. Sakamoto; S. Fujita; T. Sasagawa (IMR Press, 2020)
Purpose of Investigation: A frequent side effect of treatment with dienogest (DNG) is irregular bleeding. The present study investigated the benefits of adding traditional Japanese Kampo medicine (kyukikyogaito), which has known hemostatic effects, on DNG treatment. Materials and Methods: This retrospective study assessed the occurrence of irregular bleeding in 175 patients following oral administration of DNG (2 mg/day) for three months or more. The authors also investigated the clinical hemostatic effects of kyukikyogaito (TJ-77; 9.0 g/day) administered for 30 days in patients with irregular bleeding. Results: The frequency of irregular bleeding in patients who received DNG was 80.0%. The continuation rates for DNG treatment were 62.3% in the DNG alone group and 85.0% in the DNG plus kyukikyogaito group (p = 0.016). The efficacy of kyukikyogaito among patients with irregular bleeding was 82.6%. Conclusion: Administration of kyukikyogaito, which includes Artemisia leaf and donkey glue, was effective and could improve the continuation rate for DNG treatment by reducing irregular bleeding.